Study of Cell Behaviors on Anodized TiO2 Nanotube Arrays with Coexisting Multi-Size Diameters - Chen, Yifan; Ni, Jiahua; Wu, Hongliu; Zhang, Ruopeng; Zhao, Changli; Chen, Wenzhi; Zhang, Feiqing; Zhang, Shaoxiang; Zhang, Xiaonong (Nano-Micro Letters, 2015)
It has been revealed that the different morphologies of anodized TiO2 nanotubes, especially nanotube diameters, triggered different cell behaviors. However, the influence of TiO2 nanotubes with coexisting multi-size diameters on cell behaviors is seldom reported. In this work, coexisting four-diameter TiO2 nanotube samples, namely, one single substrate with the integration of four different nanotube diameters (60, 150, 250, and 350 nm), were prepared by repeated anodization. The boundaries between two different diameter regions show well-organized structure without obvious difference in height. The adhesion behaviors of MC3T3-E1 cells on the coexisting four-diameter TiO2 nanotube arrays were investigated. The results exhibit a significant difference of cell density between smaller diameters (60 and 150 nm) and larger diameters (250 and 350 nm) within 24 h incubation with the coexistence of different diameters, which is totally different from that on the single-diameter TiO2 nanotube arrays. The coexistence of four different diameters does not change greatly the cell morphologies compared with the single-diameter nanotubes. The findings in this work are expected to offer further understanding of the interaction between cells and materials.